Critically Ill COVID-19 Patients With Acute Kidney Injury Have Reduced Renal Blood Flow and Perfusion Despite Preserved Cardiac Function: A Case-Control Study Using Contrast-Enhanced Ultrasound. Issue 4 (April 2021) - Watchorn, James; Huang, Dean Y.; Joslin, Jennifer; Bramham, Kate; Hutchings, Sam D.
Abstract: Background: Acute kidney injury (AKI) is a common complication of COVID-19 critical illness but the pathophysiology is uncertain. Some evidence has indicated that a vascular aetiology may be implicated. We used contrast-enhanced ultrasound (CEUS) and echocardiography to study renal perfusion and global blood flow and compared our findings with measurements taken in a group of septic shock patients and healthy volunteers. Methods: Prospective case-control study. Renal perfusion variables were assessed with CEUS; macrovascular blood flow was assessed using Doppler analysis of large renal vessels; echocardiography was used to assess right and left heart function and cardiac output. Results: CEUS-derived parameters were reduced in COVID-19 associated AKI compared with healthy controls (perfusion index 3, 415 vs. 548 a.u., P = 0·001; renal blood volume 7, 794 vs. 3, 338 a.u., P = 0·04). Renal arterial flow quantified using time averaged peak velocity was also reduced compared with healthy controls (36·6 cm/s vs. 20·9 cm/s, P = 0.004) despite cardiac index being similar between groups (2.8 L/min/m 2 vs. 3.7 L/min/m 2, P = 0.07). There were no differences in CEUS-derived or cardiac parameters between COVID-19 and septic shock patients but patients with septic shock had more heterogeneous perfusion variables. Conclusion: Both large and small vessel blood flow is reduced in patients with COVID-19 associated AKI compared with healthy controls, which does not appear to be a consequence of right or left heart dysfunction. A reno-vascular pathogenesis of COVID-19 AKI seems likely. Abstract : Supplemental Digital Content is available in the text